Mapping Fifty Years of Changes in Maine's Water Quality Classifications. (2nd October 2018) - Schaffner, Rebecca; Johnson, Eileen S.; Suitor, Douglas; Courtemanch, David L.; Davies, Susan P.
Abstract: Passage of the 1972 U.S. Clean Water Act (CWA) resulted in significant improvements in water quality of the nation's freshwater systems. Maine is unique in making progress on water quality regulation through establishment of water quality classification levels that continue into the present. Starting in 1953, Maine implemented a water classification system for its surface water systems. These classification levels established minimum water quality criteria for establishing discharge requirements. Until recently, changes in classification levels were only represented in the text of state water quality standards legislation and agency regulations. This study employed geographic information systems to track changes in Maine's water classification over a fifty-year period. Our study represents one of the few spatial and temporal visualizations of water improvements as reflected in water quality classification levels. Visualization of the changes conveys the compelling story of the impact of increasingly stringent federal and state water policy coupled with advances in water treatment technologies stemming from a growing public awareness of the value of improved water quality. This study allows for a more comprehensive understanding of the policy implications of water quality improvements and can inform analyses of the social and ecological dimensions of progress in river restoration.